2016
DOI: 10.1890/15-1801.1
|View full text |Cite
|
Sign up to set email alerts
|

Higher β‐diversity observed for herbs over woody plants is driven by stronger habitat filtering in a tropical understory

Abstract: Herbaceous plants are a key component of tropical forests. Previous work indicates that herbs contribute substantially to the species richness of tropical plant communities. However, the processes structuring tropical herb diversity, and how they contrast with woody communities, have been underexplored. Within the understory of a 50-ha forest dynamics plot in central Panama, we compared the diversity, distribution, and abundance of vascular herbaceous plants with woody seedlings (i.e., tree and lianas <1 cm DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 67 publications
3
60
1
1
Order By: Relevance
“…It is expected that soil resources could be related to the composition and diversity of plant communities, and that this could be stronger for the understorey due to limiting soil resources (Gilbert & Lechowicz, ; Murphy et al, ). As expected, our results showed that soil properties were significant predictors for the phylogenetic diversity of shrubs and the functional diversity of herbs.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that soil resources could be related to the composition and diversity of plant communities, and that this could be stronger for the understorey due to limiting soil resources (Gilbert & Lechowicz, ; Murphy et al, ). As expected, our results showed that soil properties were significant predictors for the phylogenetic diversity of shrubs and the functional diversity of herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, seedling communities within 60‐m of edges were primarily structured by species turnover, suggesting strong species–environment relationships (Murphy et al. ). In addition, given that dispersal limitation is an inherent feature of many tropical forests (Wright et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Murphy et al. ) can lead to high β‐diversity via increased spatial turnover in local assemblages. With fragmentation however, sites near edges may become compositionally similar because higher ambient temperatures, desiccation, and litter fall at edges create stresses that lead to similar tree species recruiting at different sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbaceous plants contribute substantially to the diversity and abundance of forests ecosystems, particularly in temperate regions (Gilliam, 2007(Gilliam, , 2014Luo et al, 2016aLuo et al, , 2016bWang, Tang & Fang, 2007). However, interactions between herbaceous and woody plant layers in community assemblages have long been neglected in forest dynamics models, even though it is widely known that herbaceous species can impact the regeneration of tree species (Murphy, Salpeter & Comita, 2016;Thrippleton, Bugmann, Kramer-Priewasser & Snell, 2016). DNA barcoding has mainly been used for tree species in forest dynamic plots of tropical, subtropical, and temperate regions (Erickson et al, 2014;Kress et al, 2009;Pei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%